The Overview of Environmental Regulation – Brazil and the United States of America (Global Journal of Human-Social Science, 2024)
The article will present the growth of Environmental Law in the last decades and its practical repercussions with the consequent application of Environmental Law in the domestic scenarios in Brazil and in the United States of America providing a presentation of the main environmental rules such as the Federal Constitution of Brazil the Fauna Protection Law the National Water Resources Policy and the Brazilian Forest Code the National Environmental Policy Act Clean Air Act Clean Water Act combining Doctrines on environmental matters and some of the Leading Cases in Environmental Law in particular Citizens Can Preserve Overton Park Inc v Volpe 401 US 402 1971 Massachusetts v EPA 549 US 497 and Direct Action of Constitutionality ADC 42 and other Mandatory Precedents that brought new environmental debates and helped to incorporate good results in the domestic scenario of each country in the environmental field
Keywords: environment; pollution; judicialization; environmental statutes; sustainability